Contribution of glucose transport to the control of the glycolytic flux in Trypanosoma brucei - Bakker, Barbara M. (The National Academy of Sciences, 1999)
The rate of glucose transport across the plasma membrane of the bloodstream form of Trypanosoma brucei was modulated by titration of the hexose transporter with the inhibitor phloretin, and the effect on the glycolytic flux was measured. A rapid glucose uptake assay was developed to measure the transport activity independently of the glycolytic flux. Phloretin proved a competitive inhibitor. When the effect of the intracellular glucose concentration on the inhibition was taken into account, the flux control coefficient of the glucose transporter was between 0.3 and 0.5 at 5 mM glucose. Because the flux control coefficients of all steps in a metabolic pathway sum to 1, this result proves that glucose transport is not the rate-limiting step of trypanosome glycolysis. Under physiological conditions, transport shares the control with other steps. At glucose concentrations much lower than physiological, the glucose carrier assumed all control, in close agreement with model predictions.